The Ideology of Racism in Contemporary HollywoodFilms on Netflix: A Case Study on“All the Boys I’ve Loved Before” Movie - Briandana, Rizki; Marta, Rustono Farady; Mijan, Rohana; Fauzi, Eka Perwitasari (JURNAL KOMUNIKASI INDONESIA, 2022)
This study aims to analyse the ideology of racism in Hollywood films shown on Netflix. To All the Boys I’ve Loved Before is a film based on a New York Times Best Seller novel. Initially, this film had some drawbacks because almost all production houses refused to keep an Asian face as the main character in accordance with the novel. The concept of ideology in the film refers to the concept proposed by John Storey. That ideology is an ideal form of image which aims to attract attention through methods, such as those used in texts, including films as mass media products to present a certain image about the world. This study applied a qualitative text analysis method, i.e.i.e. the Semiotics method. The film was analysed through Roland Barthes’ semiotic analysis, which is known for its denotative, connotative, and mythical meanings. The signs in the film were studied in stages to get the meaning of the message and also to uncover the myths that hide behind the ideology in the film. The result shows the use of Asian faces as the main characters who are also protagonists in To All the Boys I’ve Loved Before demonstrates that the racism depicted in this film is a myth. This film also joins the ranks of Hollywood films in which Asian actors were previously thought to be unable to sell at the box office. Penelitian ini bertujuan menganalisis ideologi rasisme dalam film-film Hollywood yang ditayangkan di Netflix. To All the Boys I’ve Loved Before adalah film yang diangkat dari novel New York Times Best Seller. Pada awalnya film ini memiliki beberapa kekurangan karena hampir semua rumah produksi menolak untuk mempertahankan wajah Asia sebagai karakter utama sesuai dengan novel. Konsep ideologi dalam film mengacu pada konsep yang diusulkan oleh John Storey. Ideologi adalah bentuk citra ideal yang bertujuan untuk menarik perhatian melalui metode, seperti yang digunakan dalam teks, termasuk film sebagai produk media massa untuk menyajikan citra tertentu tentang dunia. Penelitian ini menerapkan metode analisis teks kualitatif, yaitu metode Semiotika. Film ini dianalisis melalui analisis semiotik Roland Barthes, yang dikenal dengan makna denotatif, konotatif, dan mitosnya. Tanda-tanda dalam film ini dipelajari secara bertahap untuk mendapatkan makna pesan dan juga untuk mengungkap mitos yang tersembunyi di balik ideologi dalam film. Hasilnya menunjukkan penggunaan wajah Asia sebagai karakter utama yang juga protagonis dalam To All the Boys I’ve Loved Before menunjukkan bahwa rasisme yang digambarkan dalam film ini adalah mitos. Film ini juga masuk dalam jajaran film Hollywood di mana aktor Asia sebelumnya dianggap tidak menjual di box office.